Al-Muhkamat wa al-Mutasyabihat serta Fawatih al-Suwar - Nur Fajriyatush Shobahah; Hakmi Hidayat; Choirina Khilmy Maulidia (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Allah has revealed the Qur'an as an extraordinary miracle to his servants through the intermediary of the angel Gabriel which was given to the Prophet Muhammad SAW, as a signal to carry out worship on earth. The Al-Qur'an is also a source of inspiration for every human being, because the contents of the Al-Qur'an contain concrete instructions and guidelines if there are verses that are muhkamat and mutashabihat. The Qur'an also acts as a miracle for those who believe in it because it contains verses whose meanings are zhanni or implied which have not been widely studied. Therefore, the purpose of this article was written to find out (1) the meaning of the mutasyabihat and muhkamat verses (2) the meaning of fawatih suwar (3) the attitude of the ulama regarding the mutasyabihat verse (4) the wisdom of the existence of the mutasyabihat verse. By using qualitative research methods as supporting material in writing this article.